Association of Metformin Use With Deficiency of Vitamin B-12 And Folate And Peripheral Neuropathy In Adults With Type 2 Diabetes Mellitus - Siddiqi, Fuad Ahmad; Yaseen, Laila; Ashraf, Amna; Siddiqi, Kanaz Ahmad; Ashraf, Shahzad; Khan, Imran (Journal of Rawalpindi Medical College, 2026)
Objective: This study sought to determine the association between metformin therapy, vitamin B12 and folate deficiencies, and peripheral neuropathy in adults diagnosed with Type 2 Diabetes Mellitus (T2DM). Methods: A cross-sectional study was carried out at the Department of Medicine, Tertiary Care Hospital, Rawalpindi, from November 2023 to April 2024. The study included 224 patients with T2DM based on distinct inclusion and exclusion criteria, with informed consent obtained from all participants. Data collection involved assessing diabetes duration, metformin usage, dosage, and the presence of peripheral neuropathy. Serum levels of vitamin B12, folate, and homocysteine were calculated during the evaluation. Results: Individuals taking metformin tend to have lower Serum vitamin B12 levels compared to those not using the medication. Among metformin users, 27 (69.2%) were found to have vitamin B12 deficiency, compared to 12 (30.8%) in the non-user group, indicating a significant association p=0.00. However, no significant difference in folate levels could be determined between the groups (p = 0.55). Among participants with hyperhomocysteinemia, vitamin B12 deficiency was identified in 20 (71.4%) individuals versus 8 (28.6%), with a significant p-value of 0.02. While VPT and DN4 scores were comparable between groups, the DNS score showed statistical significance, being higher in metformin users (p = 0.03). Conclusion: This study highlights the high incidence of vitamin B12 deficiency, a preventable condition, among metformin users in the evaluated population and its link to neuropathy. Future studies are warranted to evaluate the efficacy of oral vitamin B12 supplementation in managing peripheral neuropathy in this group. Patients with T2DM on metformin for more than 2 years should therefore be screened for vitamin B12 deficiency regularly. Keywords: Metformin, Peripheral Neuropathy, Diabetes Mellitus type 2, Vitamin B12